Time-efficient germ cell transplantation from goldfish (Carassius auratus) into adult common carp (Cyprinus carpio) - Vigoya, Angel Andreas Arias [UNESP]; Costa, Daniel Fernandes da [UNESP]; Oliveira, Marcos Antônio de [UNESP]; Butzge, Arno Juliano [UNESP]; Rosa, Ivana Felipe [UNESP]; Doretto, Lucas Benites [UNESP]; Martinez, Emanuel Ricardo Monteiro [UNESP]; Digmayer, Melanie [UNESP]; Nóbrega, Rafael Henrique [UNESP] (FapUNIFESP (SciELO), 2024)
Germ cell transplantation in fish is a promising technique for surrogate broodstock parents with broader application in aquaculture and conserving endangered and valuable genetic resources. Herein, we describe the establishment of an intrapapillary xenogeneic transplant of germ cells from sexually mature goldfish (C. auratus) males into common carp (C. carpio) males cytoablated with a thermochemical treatment (two doses of busulfan at 40 mg/kg at 35°C). To analyze the presence and development of donor germ cells in recipient testes, donor germ cells were labeled with PKH26, a fluorescent cell membrane dye, before transplantation. Our results demonstrated that thermochemical treatment caused effective spermatogenesis suppression and pronounced germ cell loss. Moreover, transplanted spermatogonial cells were able to colonize the recipients’ testes, resume spermatogenesis, and generate spermatozoa within eight weeks after germ cell transplantation. These findings suggested that recipient testes provided suitable conditions for the survival, colonization, proliferation, and differentiation of donor spermatogonia from a related species. This study indicated that recipients’ testes exhibited a high degree of plasticity to accept and support xenogeneic donor germ cells, which were able to form sperm in a short time frame. This approach has significant implications for assisted animal reproduction, biotechnology, conservation, and the production of valuable genetic resources and endangered fish species.
Keywords: biotechnology; common carp; goldfish; spermatogenesis; spermatogonial stem cells; teleost fish